2007
DOI: 10.1097/01.ccm.0000298122.49245.d7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementing protocol-based sepsis resuscitation in the emergency department—Results of a national survey*

Abstract: Nurse managers and physician directors of busy emergency departments representing the largest urban areas in the United States identify multiple barriers to implementing time-sensitive resuscitation to patients with severe sepsis. More than half of all respondents recognized a critical shortage of nursing staff, problems in obtaining central venous pressure monitoring, and challenges in identification of patients with sepsis as the largest roadblocks to overcome in implementing early goal-directed therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
127
1
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 38 publications
(50 reference statements)
3
127
1
6
Order By: Relevance
“…It is important to note that several barriers to adoption of a quantitative resuscitation strategy for sepsis in the ED have been identified (4,41,42). In fact, the majority of the studies in the early subgroup of this meta-analysis did not start quantitative resuscitation until intensive care unit admission leaving the possibility of some delay in treatment initiation among these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that several barriers to adoption of a quantitative resuscitation strategy for sepsis in the ED have been identified (4,41,42). In fact, the majority of the studies in the early subgroup of this meta-analysis did not start quantitative resuscitation until intensive care unit admission leaving the possibility of some delay in treatment initiation among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the reviews specifically investigated sepsis, however, the objective of this review was to determine the variation in the resuscitation goals targeted and whether this variation was associated with differences in outcome (13). Thus the present meta-analysis is markedly different from these prior systematic reviews in that we investigated the treatment effect of a quantitative resuscitation strategy only in patients with sepsis and analyzed the studies with respect to temporal timing of the intervention.It is important to note that several barriers to adoption of a quantitative resuscitation strategy for sepsis in the ED have been identified (4,41,42). In fact, the majority of the studies in the early subgroup of this meta-analysis did not start quantitative resuscitation until intensive care unit admission leaving the possibility of some delay in treatment initiation among these studies.…”
mentioning
confidence: 99%
“…ACEP has been involved as a sponsor of the campaign helping to provide guidelines and appropriate implementation for the ED setting. [3][4][5][6] Since the implementation of the campaign, there have been many articles assessing the clinical effectiveness of a more standardized approach to defining and treating the septic patient. [7][8][9][10][11][12][13] There have also been questions concerning costs, pharmaceutical involvement and a one size fits all approach.…”
Section: Surviving Sepsis Campaign Backgroundmentioning
confidence: 99%
“…20 Despite strong evidence for the efficacy and cost-effectiveness of systematic implementation of the SSC guidelines, translation of the guidelines into clinical practice has been inconsistent, incomplete, and delayed. [21][22][23][24][25] A variety of barriers to implementation of the guidelines have been identified despite the fact that clinicians' perceptions of the guidelines are generally favorable. 4,[22][23][24][25][26] These include environmental and structural bar-riers to implementation of the SSC guidelines, which require multidisciplinary, coordinated care that is delivered in a time-sensitive manner.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] A variety of barriers to implementation of the guidelines have been identified despite the fact that clinicians' perceptions of the guidelines are generally favorable. 4,[22][23][24][25][26] These include environmental and structural bar-riers to implementation of the SSC guidelines, which require multidisciplinary, coordinated care that is delivered in a time-sensitive manner. 19,22 A national survey of physicians and nurses in emergency departments located throughout the United States revealed that more than half of respondents indicated that monitoring clinical indicators of sepsis and response to therapy were significant barriers to adherence to EDGT for severe sepsis and septic shock.…”
mentioning
confidence: 99%